A NGS-Targeted Autism/ID Panel Reveals Compound Heterozygous GNB5 Variants in a Novel Patient - Malerba, Natascia; Towner, Shelley; Keating, Katherine; Squeo, Gabriella Maria; Wilson, William; Merla, Giuseppe (Frontiers in Genetics, 2018)
GNB5 encodes the Guanine Nucleotide Binding protein subunit 5, which is involved in inhibitory heterotrimeric G protein coupled signaling. Homozygous and compound heterozygous pathogenic variants in GNB5 have been recently associated with a spectrum of clinical presentations varying from a severe multisystem form of the disorder including intellectual disability, early infantile developmental and epileptic encephalopathy, retinal abnormalities and cardiac arrhythmias (IDDCA) to a milder form with language delay, attention-deficit/hyperactivity disorder, cognitive impairment, with or without cardiac arrhythmia (LADCI). Approximately twenty patients have been described so far; here we report a novel case of a 2.5 year old female who is a compound heterozygote for a frameshift and a missense variant in the GNB5 gene. Her clinical presentation is consistent with a moderate phenotype, corroborating the direct correlation between the type and pathogenic mechanism of the GNB5 genetic variant and the severity of related phenotype.